MENUMBUHKAN MINAT GEN Z PADA PEMBELAJARN SEJARAH - Febriyanti, Intan; Syarifuddin; Pamulaan, Alif Bahtiar (BANDA HISTORIA: Jurnal Pendidikan Sejarah dan Studi Budaya, 2025)
This research examines how the use of social media platforms, especially TikTok and Twitter, can influence Generation Z's interest in history. Generation Z, accustomed to digital technology, is often less interested in historical subjects that are considered irrelevant. However, by adapting existing content formats on TikTok and Twitter that are more dynamic and easily accessible to Gen-Z, history can be presented in a more interesting way. TikTok, with its short videos, provides an opportunity to present historical facts visually and creatively, while Twitter allows the exchange of ideas and discussions based on trending historical topics. This research method uses a qualitative approach with content analysis from various accounts that discuss the history of the two platforms. The findings of this research show that with a more relaxed and interactive approach, Generation Z's interest in history can increase, especially if the content presented is able to connect historical events with contemporary issues that are relevant to them. Therefore, TikTok and Twitter not only have the potential to convey historical information, but also to create more interesting learning, and are appropriate to the digital lifestyle of Generation Z